The double burden of COVID-19 and Israeli military rule on persons with disabilities in the West Bank of the occupied Palestinian territory - Mitwalli, Suzan; Kiwan, Dina; Abdul-Samad, Lina; Giacaman, Rita (Frontiers in Psychology, 2022)
Background: The COVID-19 pandemic has enormous negative effects on people’s lives. People with disabilities who have been made vulnerable and who tend to face significant barriers in accessing public services are likely to be affected even more. This study aims to shed light on the impact of the COVID-19 pandemic on people with disabilities (PWDs) with special attention to their ability to access public services in the West Bank region of the occupied Palestinian territory. Methods: This qualitative study was conducted between March 2021 and October 2021. The study was divided into two phases. The first phase consisted of interviews with people with different disabilities, while the second phase targeted policymakers and stakeholders in discussion of the results of the first phase. A total of 16 interviews with people with different types of disabilities (7 males, 9 females) were conducted via telephone. For the second phase, a total of 6 interviews were conducted with stakeholders most responsible for addressing the issue of disability and the needs of people with disabilities in the West Bank. Analytical memos were prepared for all interviews. Main themes and subthemes were identified by reading and re-reading memos and transcripts until themes and subthemes emerged. Results: All participants agreed that the COVID-19 pandemic had affected all aspects of life for all groups of people, including PWDs. The effects of the pandemic exacerbated the overall living conditions and access to basic services for PWDs. The results show that access to public transportation, public services, and to health services was all interrupted during the pandemic. This was compounded by deterioration of the financial situation for people with disabilities which further worsened their access. The stakeholders’ interviews confirmed and explained the findings as mainly due to lack of prioritization of PWD’s rights and needs. Conclusions: The study emphasized that most of the reported barriers to accessing essential services were intensified during the pandemic. Furthermore, the results show that PWDs and their needs are not considered a priority by the Palestinian Authority, exacerbated by the Israeli occupation. Our findings underline the importance of including PWDs in any future crisis planning.